If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x^2-11x-33=0
a = 4; b = -11; c = -33;
Δ = b2-4ac
Δ = -112-4·4·(-33)
Δ = 649
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:x_{1}=\frac{-b-\sqrt{\Delta}}{2a}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-11)-\sqrt{649}}{2*4}=\frac{11-\sqrt{649}}{8}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-11)+\sqrt{649}}{2*4}=\frac{11+\sqrt{649}}{8}
| 2w=1/9 | | (1/5)x+3=6 | | .333333333(6x+12)-2(x-7)=19 | | p-6=p-1+p-10 | | 25−6x=14+5x | | 4x+96=4x-24 | | 1.9s+6=3.1-6 | | 8=2r-5r | | ^x+2=11 | | 3x+-2(x+1)=-7 | | d/1.3=1.24 | | 3h-4=h+6 | | 13b-3b=20 | | 18p^2=12-15p | | 27=26p-1 | | -854t^2+64000t-150000=0 | | z÷11.4=6 | | 4=6r | | 5(x-3)+3=-12 | | 5x÷-x÷6=14 | | -854t^2+64000-150000=0 | | a+.93=1.42 | | 3(x+1)+2=x+9 | | 4-1/2a=6-a | | q^2+49q+144=0 | | -12=6(x+6)+6x | | q^2+49+144=0 | | 5(3x+6)=-14+29 | | 5x÷2-x÷6=14 | | 1/2x-3/4=2/3x+2 | | -79=-y–6y–16 | | 3(x+4)=4x+12-6 |